2011
DOI: 10.1002/cyto.a.21094
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric assay using two fluorescent proteins for the function of the internal ribosome entry site of hepatitis C virus

Abstract: The initiation of translation in hepatitis C virus (HCV) occurs at the internal ribosome entry site (IRES) located at the 5 0 -end of its genomic RNA. To study the function of HCV IRES, we constructed a reporter plasmid that generates a bicistronic mRNA encoding two fluorescent proteins: cap-dependent DsRed2 and IRES-dependent Azami Green (AG). We introduced the plasmid into Huh7.5.1 and HEK293 cells and measured the relative IRES activity from the ratio of AG's signal to DsRed2's in individual cells using flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Thus, we wondered if our findings could be replicated in a non-hepatic and non-lymphoid cell line such as HEK293T cells. HEK293T cells are not permissive to HCV infection [ 71 ], yet are supportive of HCV IRES function [ 13 , 46 , 72 , 73 ]. Furthermore, a previous report from our laboratory shows that the overexpression of PTB1 enhances HCV IRES activity in HEK293T cells [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we wondered if our findings could be replicated in a non-hepatic and non-lymphoid cell line such as HEK293T cells. HEK293T cells are not permissive to HCV infection [ 71 ], yet are supportive of HCV IRES function [ 13 , 46 , 72 , 73 ]. Furthermore, a previous report from our laboratory shows that the overexpression of PTB1 enhances HCV IRES activity in HEK293T cells [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies reporting on direct comparison of dual luciferase with dual fluorescence reporters were rare. At least for multiple HCV IRES sequence mutants both reporter configurations provided identical results in HEK293 and Huh-7 cells [ 164 ]. In the same study, stimulation of cells with IFNγ for 36 h demonstrated a higher sensitivity of the dual luciferase system in comparison to the fluorescent reporter.…”
Section: Resultsmentioning
confidence: 99%
“…Although CAT/βGal reporters see limited use in recent times, their susceptibility to cryptic splicing was shown to be lower than Fluc/Rluc reporters [ 109 ]. Fluorescent reporters can be used for flow cytometric applications; however, reporter protein maturation times are substantially longer [ 222 ], and therefore sensitivity was demonstrated to be lower [ 164 ]. To our knowledge, newer luciferases, such as NanoLuc derived from Oplophorus gracilirostris [ 233 ], have not yet been used in bicistronic reporter configurations.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense the discovery of novel technologies and moreover their subsequent applications have become important in laboratory and field studies. As an example, innovations in high-throughput single cell analysis for diagnostic purposes but also for functional analysis and drug discovery are today available in order to analyze pathogenic organisms such as the viruses Hepatitis C [1], influenza [2], or HIV [3] as well as bacteria like Mycobacterium tuberculosis [4] or Staphylococcus aureus [5]. The SELEX technique (Systematic Evolution of Ligands by Exponential Enrichment) was originally discovered by Gold and Szostak [6, 7].…”
Section: Introductionmentioning
confidence: 99%